The servant of two masters: Italian diplomats in World War II. Story of a diplomatic civil war and its implications and consequences on post-war foreign policy - Marsili, M. (Journal of Modern Italian Studies, 2022)
Diplomacy has played a key role in conflicts since ancient times. Over time, the role of diplomatic agents has changed, to take on, gradually, greater importance especially in wartime. This article focuses on the activities of the Italian foreign service in World War II and on the role of diplomats during the civil war that followed the fall of Fascism and the subsequent armistice with the Allies. In this dramatic context, some diplomats confirmed their loyalty to the king, while others joined the new-born Italian Social Republic, a puppet state ruled by Mussolini under the protection of Nazi Germany. Somewhere, two Italian diplomatic representations coexisted shortly. A page in the history of diplomacy, unknown to wide audience, that this contribution aims to bring to light. The paper strives to draw conclusions on the implications and consequences of this 'diplomatic civil war' on post-war Italian foreign policy.